Criminal Proceedings Law Improvements for Justice Witnesses in Albania (European Journal of Multidisciplinary Studies, 2021)
In the framework of the constitutional justice reform of year 2016, “Constitutional reform in Albania of year 2016 determined fundamental amendments by improving justice system.” (Balla, 2017, p. 368), there are undertaken to be improved important justice laws. Therefore, fundamental amendments are made on the Criminal Proceedings Code (CPC) on year 2017. These amendments consisted in general and specially to enable the implementation of government policy, for the establishment of new institutions and the strengthening of existing ones, in the fight against corruption and the consolidation of the justice system. At the same time, the amendments aim to address the most obvious issues and problems encountered in practice. Correspondingly, the constitutional amendments and the adoption of other laws, necessary to implement them, brought the need to unify and harmonize these amendments in the CPC. In particular, the new regulations aim to determine the prosecutor's independence in the criminal proceedings, the establishment of the Special Prosecution Office, the jurisdiction of the High Court and the change in the subject matter jurisdiction of the Court of Corruption and Organized Crime. Through this paper it is addressed the treatment of new standards and institutes that are regulated in the CPC. How do they stand compared to European standards such as the jurisprudence of the ECtHR and international law, as well as the jurisprudence of International Criminal Court (ICC). The paper aims to address issues related to the rights of defendants, the legal position of the victims and especially the treatment of the most favorable legal status of protected witnesses and collaborators of justice.